Method for measuring chemical components of cold-pressed block by X fluorescence melting method
The process of measuring the chemical composition of the cold-pressed chunk is simplified by the X-fluorescence melting method, solving the problems of cumbersome steps of the existing methods and the use of a large number of chemical reagents, and achieving efficient, accurate and environmentally friendly detection results.
Patent Information
- Application Number
- CN202411839064.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The existing cold press chemical composition measurement methods are cumbersome, time-consuming and labor-intensive, difficult to adapt to the tight production rhythm, and use more than 20 chemical reagents, which increases the physical harm to the operators.
The chemical composition of the cold press was measured by X-fluorescence melting method, and glass sheets were prepared by burning and melting, and detection was performed using X-fluorescence instruments, which simplified the operation steps and reduced the use of chemical reagents.
It improves detection efficiency, reduces labor and material costs, reduces the use of chemicals, and is highly accurate, environmentally friendly and efficient, and can quickly and accurately determine the main chemical components of cold presses.
Smart Images

Figure BDA0005187517210000021 
Figure BDA0005187517210000061 
Figure BDA0005187517210000072
Abstract
Description
Technical Field
[0001] The invention relates to the determination of the composition of products recycled from metallurgical steelmaking solid wastes, and specifically provides a method for determining the chemical composition of cold pressed blocks using an X-ray fluorescence melting method. Background Art
[0002] Cold pressed briquettes are products of solid waste recycling from metallurgical steelmaking. They are made by adding binders to converter dust removal ash, converter mud, etc., mixing them evenly, and then pressing them into briquettes. The recycling of solid waste creates profit value for steel mills and reduces the discharge of solid waste. The chemical composition of cold pressed briquettes mainly contains iron, calcium, magnesium, silicon, manganese, zinc, lead, aluminum, phosphorus, and titanium, among which iron and carbon often exist as partial single substances. Existing methods for measuring cold pressed briquettes include titration, colorimetry, atomic absorption, etc. Among them, iron, calcium, and magnesium are determined by separate titration, manganese, zinc, lead, and titanium are determined by atomic absorption, and silicon and phosphorus are determined by colorimetry. The various measurement methods are cumbersome and require multiple people to complete, making it difficult to adapt to the current tight production rhythm.
[0003] The determination of the chemical composition of existing cold pressed blocks is to melt with alkali, extract with hydrochloric acid, and obtain the mother liquor after constant volume. Part of the solution is separated from the mother liquor to determine its components. The method for determining the iron content is to reduce a large amount of trivalent iron with stannous chloride, use sodium tungstate as an indicator, and use titanium trichloride to reduce the remaining trivalent iron to generate "tungsten blue". Under the catalysis of copper ions, air oxidation is carried out until the blue disappears, and sulfuric acid and phosphoric acid mixed acid is added. Sodium diphenylamine sulfonate is used as an indicator and titrated with potassium dichromate standard solution. The calcium and magnesium content is to mask the iron, aluminum, manganese and other ions with triethanolamine, and in a strong alkaline medium, calcium indicator is used as an indicator, and the amount of calcium oxide is titrated with EDTA standard solution. Take another part of the test solution, mask the iron, aluminum, manganese and other ions with triethanolamine, and in an ammonia buffer solution, use acid chromium blue K and naphthol green B as mixed indicators, and titrate the calcium oxide and magnesium oxide content with EDTA standard solution. The contents of manganese, zinc, lead and titanium are measured by removing part of the mother liquor, diluting it with water to a certain volume, and then entering the atomic absorption for detection and measurement of their percentages. The contents of silicon and phosphorus are measured by taking part of the mother liquor. Phosphorus forms a complex with bismuth and ammonium molybdate in a nitric acid medium, and is reduced to molybdenum blue with ascorbic acid. Silicon also forms silicomolybdenum heteropoly acid with ammonium molybdate in a nitric acid medium, and oxalic acid-sulfuric acid mixed acid is added to eliminate the interference of phosphorus and arsenic, and it is reduced to silicomolybdenum blue with ammonium ferrous sulfate. The absorbance is measured at the wavelengths of 700nm and 680nm of the spectrophotometer, respectively.
[0004] The existing cold-pressed block composition determination steps are numerous, time-consuming and labor-intensive, and require at least three people to complete the operation. It cannot meet the current tight production rhythm and requires the use of more than twenty chemical reagents, which increases the degree of harm to the health of operators. The existing method has low detection efficiency and is not environmentally friendly. Summary of the invention
[0005] The present invention relates to the technical field of metallurgical chemical analysis and testing, and in particular to a method for determining the chemical composition of a cold pressed block by an X-ray fluorescence melting method. The X-ray fluorescence melting method is used to determine the chemical components of iron, calcium, magnesium, silicon, manganese, zinc, lead, aluminum, phosphorus, titanium and the like in the cold pressed block, and the steps are relatively simple, which reduces the tedious manual operation, improves the detection efficiency, reduces the labor and material costs, reduces the use of chemicals, and has high accuracy, environmental protection and high efficiency.
[0006] Specifically, a method for determining the chemical composition of a cold pressed block by an X-ray fluorescence melting method comprises taking a cold pressed block sample, burning it, and then melting it, pouring the sample melt into a mold to make a glass sheet; and using an X-ray fluorescence instrument to determine the chemical composition present in the cold pressed block sample on the obtained glass sheet.
[0007] The calcination treatment is to place the cold pressed block sample in a muffle furnace and calcine it at 750° C. for 30 minutes.
[0008] In the melting, in a platinum-gold crucible, the cold pressed block sample is mixed with cobalt trioxide and a solvent, and then a mixed solution of LiNO3 and LiBr is added, and then heated to melt. In one embodiment, after preheating at the high-temperature melting furnace for 1 minute, it is pre-oxidized in a melting furnace with a furnace temperature of 1050°C for 10 minutes, and after the gas is completely volatilized, a clean platinum-gold crucible is sent into the furnace, and when the furnace temperature rises to 1050°C again, it is melted for 10 minutes.
[0009] In the mixed solution of LiNO3 and LiBr, the concentration of LiNO3 is 500 g / L and the concentration of LiBr is 100 g / L.
[0010] The measurement conditions of the X-ray fluorescence instrument are as follows:
[0011]
[0012] Advantages of the present invention:
[0013] 1. The cold pressed block contains a certain amount of iron and carbon. In order to avoid the corrosion of these two elements to the precious metal crucible, the present invention first burns the cold pressed block sample at high temperature to volatilize the carbon and oxidize the iron and other elements, thereby protecting the platinum gold crucible. Then, the cold pressed block is placed in a platinum gold crucible and melted with a flux to make a glass sheet sample. The glass sheet is subjected to X-ray fluorescence detection under set conditions, and the detection data is read out on a computer. The X-ray fluorescence melting method can detect all elements at one time without separate detection, which greatly improves the detection efficiency.
[0014] 2. Compared with the traditional detection method, the present invention has fewer steps and fewer influencing factors, and has better accuracy and precision. The working curve coefficient is above 0.99, the deviation between the standard sample detection value and the certified value is less than the critical difference of the similar national standard, and the deviation between the X-ray fluorescence detection value and the detection value of other methods is also small, which proves that the curve control of this method is better. And the chemical reagents used are less, and nearly 20 kinds of chemicals are reduced compared with titration, colorimetry, and atomic absorption, which greatly reduces the harm of chemicals to operating employees.
[0015] 3. There is no corresponding standard sample for cold pressed blocks. Standard samples with similar matrix are selected and mixed in precious metal crucibles and made into glass sheets through melting furnaces. X-ray fluorescence working curves are established. Production samples and glass sheets made under the same conditions are tested on the established working curves. The mineral effect caused by the particle size is eliminated by the melted materials, making the chemical states of various elements consistent. After the melt is measured on the instrument, the computer reads the corresponding intensity, and compares it with the standard sample intensity to calculate the corresponding percentage.
[0016] 4. The present invention can accurately and quickly determine the main chemical components of cold-pressed blocks. At the same time, it only needs one person to complete it by himself, without the need for multiple people to cooperate in the operation. It can reduce the number of people operating at the same time, reduce the labor intensity of employees, solve the disadvantages of the existing detection methods that are time-consuming, labor-intensive and environmentally unfriendly, and greatly meet the existing tight production rhythm.
[0017] 5. The detection method formulated by the present invention can simultaneously determine the chemical composition of iron, calcium, magnesium, silicon, manganese, zinc, lead, aluminum, phosphorus and titanium of the cold pressed block without separate detection. The operation is simple and there is no need to use too many chemical reagents, which saves a lot of manpower and material resources and the use of chemical reagents. It provides data support for the recycling of solid wastes such as converter dust removal ash and converter mud, which are raw materials for cold pressed blocks, and increases benefits. DETAILED DESCRIPTION
[0018] The present invention will be further described below in conjunction with specific embodiments.
[0019] 1 Materials and Reagents
[0020] 1.1 Standard sample: a certified industry standard sample with a matrix similar to the analytical sample. It is used to establish the X-ray fluorescence instrument detection curve and monitor daily testing. Its chemical composition covers the detection range of the analytical sample.
[0021] 1.2 Mixed flux: high-grade pure, lithium tetraborate and lithium metaborate in a mass ratio of 2:1, placed in a porcelain plate wrapped in tin foil and baked at 600℃ for 4 hours, cooled and stored in a desiccator for later use.
[0022] 1.3 Oxidant: lithium nitrate (500 g / L), analytical grade. Weigh 500.0 g of lithium nitrate into deionized water, dilute to 1000 mL, and mix well.
[0023] 1.4 Release agent: lithium bromide (100 g / L), analytical grade. Weigh 100.0 g of lithium bromide in deionized water, dilute to 1000 mL, and mix well.
[0024] 1.5 Mixed solution: Mix lithium nitrate (500 g / L) and lithium bromide (100 g / L) solutions in a reagent bottle, shake well and set aside.
[0025] 1.6 Internal standard substance: Cobalt trioxide, high purity, dried at 105°C for 1 hour, cooled in a desiccator and set aside for use.
[0026] 1.7 Crucible washing solution: nitric acid (1+5), analytical grade.
[0027] 1.8 Argon-methane gas composition (mol / mol): 10% methane, the balance gas is argon.
[0028] 2 samples
[0029] Cold pressed block samples are prepared according to GB / T10322.1, and the samples should be sieved through a 0.125 micron sieve. After sieving, the samples are dried in an oven at 105°C, cooled in a glass drying tower filled with color-changing silica gel, and mixed with a spoon after reaching room temperature, and 0.7000g±0.0002g of the sample is weighed.
[0030] 3. Instruments and Equipment
[0031] 3.1 Wavelength dispersive X-ray fluorescence spectrometer: a simultaneous or sequential wavelength dispersive spectrometer that meets the requirements of “JJG810 National Metrology Verification Procedure of the People’s Republic of China - Wavelength dispersive X-ray fluorescence spectrometer”.
[0032] 3.2 High temperature melting furnace: The high temperature melting furnace can maintain at least 1100℃, and it is best to be able to swing automatically. It has a crucible rotation of 30r / min.
[0033] 3.3 Muffle furnace: can maintain above 800℃.
[0034] 3.4 Platinum-gold crucible and mold: The material is 95% platinum + 5% gold, the crucible is 30mL~40mL, and the bottom of the mold is flat and smooth.
[0035] 3.5 Crucible clamp: The clamp head is coated with platinum gold.
[0036] 3.6 Weighing tools: electronic balance: accuracy 0.0001g; the weighing spoon is an ordinary laboratory stainless steel medicine spoon, and the sample brush is a white oil painting brush.
[0037] 3.7 Pipette: 5mL, adjustable range.
[0038] 4. Glass Slide Preparation
[0039] 4.1 Sample pretreatment: Weigh 0.7000g (accurate to 0.0002g) of the cold pressed sample from 2.2.2 and place it flat on a porcelain boat, then place it in a muffle furnace and heat it to 750℃ for 30 minutes. Take it out and cool it to room temperature, then sweep it into a platinum-gold crucible.
[0040] 4.2 Sample melting step: Weigh 0.1000g (accurate to 0.0002g) of cobalt trioxide and add it to the platinum-gold crucible containing the burned sample in 4.1, and then put it into the platinum-gold crucible with 7.0000g (accurate to 0.0005g) of flux (1.2) weighed. Carefully mix the sample and flux with a glass rod, and use a brush to sweep the sample and flux attached to the glass rod into the crucible. Use a pipette to measure 1.00mL of the mixed solution (1.5) of [LiNO3 (500g / L) + LiBr (100g / L)] and evenly add it to the crucible. , place the crucible at the mouth of the high-temperature melting furnace to preheat for 1 minute, then put the crucible into the melting furnace with a temperature of 1050℃ for pre-oxidation for 10 minutes, and after the gas evaporates, send the clean platinum gold crucible into the furnace. When the furnace temperature rises to 1050℃ again, start the rocking button and start the timing. After the sample is melted for 10 minutes, turn off the rocking button, pour the sample melt into the mold, and demold the glass piece after cooling for 4 minutes. Visually inspect the glass piece for defects such as unmelted matter, crystals or bubbles. Defective melting samples should be discarded and qualified melting samples should be re-prepared.
[0041] Put the intact glass pieces into the sample bag, mark it and put it into the desiccator for testing.
[0042] Be careful not to let the glass rod touch the crucible to avoid scratching the crucible and affecting the flow of the sample. During the whole process, the brush, pipette, crucible tongs, etc. must not be lost or contaminated.
[0043] 5 Measurement conditions
[0044] Select appropriate measurement conditions according to the type of X-ray fluorescence instrument, sample type, and content of analyzed elements. The main measurement conditions are shown in Table 1.
[0045] Table 1 Measurement conditions
[0046]
[0047]
[0048] 6 Drawing of calibration curves for each element
[0049] After determining the analysis conditions, select a certain number of standard substance samples with similar component contents to the analyzed samples. The content of the standard substances should cover the detection range of the analyzed samples, and each component should have a high and low standard. The standard samples required for the calibration curve are shown in Table 2. Then, glass slides are made according to the steps in 4. Each sample should be measured at least 3 times, and the calibration curve is drawn with the certified values of the elements in the standard samples and the average value of the measured X-ray fluorescence intensity. The percentage concentration of the element is the horizontal axis, and the corresponding intensity is the vertical axis. The working curve of iron is drawn with the X-ray intensity ratio of the iron analysis element and the internal standard element cobalt and the percentage of iron. The calibration curve parameters are shown in Table 3. The curve has 10 element coefficients R 2 They are all above 0.99, indicating that the working curve has good linearity, less interference, and fully meets the detection requirements.
[0050] Table 2 Standard samples and component contents (%) required for calibration working curve
[0051]
[0052]
[0053] Table 3 Working curve parameters
[0054]
[0055] 7 Composition detection of cold pressed samples
[0056] Each time before testing the composition of the cold pressed block, the working curve should be confirmed with the standard material made of glass sheets. Generally, the high and low standards covering the analysis sample are used for confirmation. The confirmed test value should meet the allowable deviation specified in the national standard GB / T6730.87. If the identification value of the standard material and the test value do not exceed the standard range, the cold pressed block sample test is carried out; if it exceeds the specified allowable deviation, the curve should be corrected by manual curve adjustment or drift correction, and the standard material should be tested after adjustment. After stabilization, the sample test is carried out; if the deviation occurs frequently, the hardware problem should be considered.
[0057] 8 Method Accuracy Experiment
[0058] Three standard samples were selected for component detection according to steps 4 and 7. Two parallel samples were prepared for each sample and entered into the X-ray fluorescence instrument to detect the component. The average of the two results was compared with the certified value of the standard substance. The deviation of the chemical composition of each element was within the critical difference range of GB / T6730.87 "Determination of total iron and other multi-element content of iron ore by wavelength dispersive X-ray fluorescence spectrometry (cobalt internal standard method)", as shown in Table 4. The deviation of each component met the standard requirements.
[0059] Table 4 Accuracy test of standard substances (%)
[0060]
[0061] Two cold pressed block analysis samples were taken and measured by titration, colorimetry and atomic absorption respectively, and compared with the measured values by X-ray fluorescence melting method. As shown in Table 5, the detection deviation is less than the measurement reproducibility specified in GB / T6730.87 standard.
[0062] Table 5 Cold pressed block sample detection accuracy experiment (%)
[0063]
[0064] 9. Precision experiment
[0065] A cold pressed block sample was used to make 10 glass sheets using the method established by the present invention. Each glass sheet was measured once, and 10 sets of data were used for precision test. The relative standard deviation of each component was calculated, and the results are listed in Table 5. The smallest relative deviation was 0.17% for iron with the highest content. The largest relative standard deviation was 4.76% for lead with a relatively low content. The relative standard deviations of the 10 components were all less than 5%. The precision of the method of the present invention can meet the production requirements.
[0066] Table 5 Precision test (%)
[0067]
Claims
1. A method for determining the chemical composition of cold pressed blocks by X-ray fluorescence melting method, characterized in that: The cold pressed block sample is taken, burned and then melted; the sample melt is poured into a mold to form a glass sheet; the glass sheet is used to measure the chemical components in the cold pressed block sample using an X-ray fluorescence instrument.
2. The method for determining the chemical composition of cold pressed blocks by X-ray fluorescence melting method according to claim 1, characterized in that: The calcination treatment is to place the cold pressed block sample in a muffle furnace and calcine it at 750° C. for 30 minutes.
3. The method for determining the chemical composition of cold pressed blocks by X-ray fluorescence melting method according to claim 1, characterized in that: During the melting, in a platinum-gold crucible, the cold pressed block sample is mixed with cobalt trioxide and a solvent, and then a mixed solution of LiNO3 and LiBr is added, and then heated to melt.
4. The method for determining the chemical composition of cold pressed blocks by X-ray fluorescence melting method according to claim 3, characterized in that: The heating and melting is first preheated at the high-temperature melting furnace for 1 minute, and then pre-oxidized in the melting furnace at a temperature of 1050°C for 10 minutes. After the gas is evaporated, a clean platinum-gold crucible is sent into the furnace. When the furnace temperature rises to 1050°C again, melting is carried out for 10 minutes.
5. The method for determining the chemical composition of cold pressed blocks by X-ray fluorescence melting method according to claim 3, characterized in that: In the mixed solution of LiNO3 and LiBr, the concentration of LiNO3 is 500 g / L and the concentration of LiBr is 100 g / L.
6. The method for determining the chemical composition of cold pressed blocks by X-ray fluorescence melting method according to claim 1, characterized in that: The measurement conditions of the X-ray fluorescence instrument are as follows:
Citation Information
Patent Citations
Method for analyzing components of iron ore by using X-ray fluorescence spectrum
CN101526488A
X fluorescence determination method for contents of zinc, iron and titanium in dry dedusting ash of blast furnace
CN109142412A
Sample compound method for alloy iron fluorescentx-ray analysis and the sample pretreatment methodthereof
KR1020040027087A